Literature and the Environmental Humanities: a theoretical framework - Elia, Annamaria (Status Quaestionis, 2024)
Since the second half of the 20th century, a growing concern about the environment and climate change has been raised across different academic fields. As for literary studies, the debate about ecocriticism nourished the flourishing of new theories and ideas coming from the intersection of natural sciences and humanities. Despite the hegemony of Anglophone research, drawing from more multicultural contexts environmental studies seem nowadays to converge more and more towards the interdisciplinary – and yet non unitary – field of the Environmental Humanities. This article intends to frame a comprehensive overview of the major con-temporary ecocritical theories from a comparative perspective, particularly focusing on the contribution that literature brings to the wider context of Environmental Humanities and in response to the epistemological and ontological challenges posed by the Anthropocene. In doing so, it particularly focuses on three main key concepts: nature, agency, and scales.